IMPLEMENTASI TUJUAN PEMBANGUNAN BERKELANJUTAN INDUSTRI, INOVASI DAN INFRASTRUKTUR DI KABUPATEN BOGOR - Aminda, Renea Shinta; Aminda, Annisa (JPMUJ, 2024)
Sustainable Development or often known as Sustainable Development Goals is an agreement by world leaders regarding a global action plan, and Indonesia is included in this global action plan agreement. SDGs are a development agenda that is expected to be able to face existing challenges. This was created to end poverty, reduce inequality, and protect the environment. The action plan in the SDGs contains 17 Goals and 169 Targets which are expected to be achieved by 2030. Bogor Regency in the development of Industry, Infrastructure, and Innovation, where in large industries in Bogor Regency itself in the 2017-2019 Bogor Regency BPS data for medium and large industries for the year in 2017 there were 1916 industries, then in 2017 there were 1917 industries and in 2019 there were 1930 industries. This growth in industrial development shows how industrial development in Bogor Regency can proceed as we enter the era of digitalization and increasing the number of industries will also affect Bogor Regency's GDP. The targets for 2022 and 2023 are for the proportion of added value in the manufacturing industry sector and the growth rate of manufacturing GDP, however, the proportion of added value for the manufacturing industry in Bogor Regency is projected to have a constant achievement during 2023-2026 with a figure of 43.16%. The GDP growth rate for the manufacturing industry in Bogor Regency is projected to have a constant achievement during 2023-2026 with a figure of 4%.